Relationship of Confidence with Interpersonal Communication - Diani Maulidya; Yulidar Ibrahim (Jurnal Neo Konseling, 2019)
The success of interpersonal communication depends a lot on the quality of one's concepts, both positive and negative. People who lack confidence will tend to avoid communication. This is because a person's confidence can actualize all of his potentials. Therefore the problem to be examined in this study is "Is there a relationship between self-confidence and interpersonal communication?". This research is included in the type of quantitative research. The method used in this quantitative research is correlational. This research was conducted in the odd semester (IX) 2019 at SMAN 3 Bukittinggi. The population of all students of class X and class XI of SMAN 3 Bukittinggi is 588 students. To determine a large number of populations used to be sampled, this study uses Proportional Stratified random sampling. The number of sample members is determined through the Slovin formula. So, the sample was 233 students. By analyzing the correlation test using a computer program Statistics Product Service Solution (SPSS) for Windows Release 20.0 or using the Pearson Correlation formula. The results showed that there was a relationship between self-confidence and interpersonal communication, with a coefficient of 0.562 with a significant value of 0,000 with a total of 233 student respondents, meaning that there was a significant positive relationship between confidence and interpersonal communication.